Cold-induced precipitation of a monoclonal IgM: A negative activation enthalpy reaction - Meliga, S.; Farrugia, W.; Ramsland, Paul; Falconer, R. (American Chemical Society, 2013)
Cold-induced precipitation of a monoclonal IgM cryoglobulin isolated from a patient with Waldenström's macroglobulinemia was observed to have a negative activation enthalpy. The rate of the reaction increased, as the temperature decreased. Differential scanning calorimetry of the monoclonal IgM showed precipitation as an inverted peak during a downward temperature scan. The transition temperature was between 14 and 15 °C and was possibly concentration dependent. At temperatures below the transition the precipitation was best described by second-order kinetics. The difference in change in enthalpy between precipitation and disassociation suggests that cold-induced precipitation had a fast precipitation stage followed by a slower consolidation reaction. Negligible curvature of the Eyring plot suggested the precipitation reaction was dominated by van der Waal forces and hydrogen bonding. Conversely, during an upward temperature scan, disassociation was observed as a positive enthalpy peak. This reaction had two stages, a reaction undoing consolidation followed by heat-induced disassociation that had first-order kinetics.